PENGARUH KOMPENSASI DAN DISPLIN KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA PATRIOT BEKASI - Siwi Nur Indriyani (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
The purpose of this study is to analyze the effect of compensation and work discipline on the performance of PDAM Tirta Patriot employees. This type of research is included in the category of causal associative quantitative research. The source of research data is primary data using a questionnaire with a Likert point scale 5. The sampling technique used is a saturated sample. The research was conducted of PDAM Tirta Patriot employees. The analytical technique used in this study is multiple linear regression analysi,. The results of the analysis show that compensation and work discipline either partially or simultaneously have a positive and significant effect on employee performance.